Juridical Concept of Intellectual Property Rights as Endowments - Rustam Magun Pikahulan (Al-Mizan (e-Journal), 2020)
The focus of the study in this article is regarding the position of Intellectual Property Rights as the object of waqf from a juridical perspective. This article is included in the type of normative legal research because in this article the author makes law the subject of study, and the approach used in this article is of course the legal approach. Based on the results of the study and analysis, the authors conclude that, juridically, the Endowment of Intellectual Property Rights (IPR) has obtained legal legitimacy in Indonesia. In addition to being regulated in Law Number 41 of 2004 concerning Waqf, IPR waqf has also been confirmed in several laws in the field of IPR, both before the Waqf Law was issued and after the Waqf Law was issued. Intellectual Property Rights can be transferred as long as the transition does not conflict with the prevailing laws and regulations in society, including by way of waqf. This is because IPR is a movable intangible object, IPR material appears as a form of appreciation for intellectual activities that are born from human thought to create something new or original, both in the fields of science, technology, literature and the industrial sector.